2006
DOI: 10.1111/j.1574-6968.2006.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurance ofStaphylococcus nepalensisstrains in different sources including human clinical material

Abstract: Five isolates of coagulase-negative staphylococci were obtained from human urine, the gastrointestinal tract of squirrel monkeys, pig skin and from the environment. All key biochemical characteristics of the tested strains corresponded with the description of Staphylococcus xylosus species. However, partial 16S rRNA gene sequences obtained from analysed strains corresponded with those of Staphylococcus nepalensis reference strains, except for two strains which differed in one residue. Ribotyping with EcoRI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…BLAST analysis of this sequence found 94% homology to an uncultured Firmicute isolate from a DGGE band produced from a chicken litter sample [76]. There were also a number of BLAST hits to Staphylococcus nepalensis isolated from the GI tracts of monkey and pigs [4]. In the same study, Novakova et al [4] found that it was impossible to differentiate between S. xylosus and S. nepalensis by biological tests alone and additional 16S rRNA gene sequencing was required to differentiate these two species.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…BLAST analysis of this sequence found 94% homology to an uncultured Firmicute isolate from a DGGE band produced from a chicken litter sample [76]. There were also a number of BLAST hits to Staphylococcus nepalensis isolated from the GI tracts of monkey and pigs [4]. In the same study, Novakova et al [4] found that it was impossible to differentiate between S. xylosus and S. nepalensis by biological tests alone and additional 16S rRNA gene sequencing was required to differentiate these two species.…”
Section: Resultsmentioning
confidence: 94%
“…There were also a number of BLAST hits to Staphylococcus nepalensis isolated from the GI tracts of monkey and pigs [4]. In the same study, Novakova et al [4] found that it was impossible to differentiate between S. xylosus and S. nepalensis by biological tests alone and additional 16S rRNA gene sequencing was required to differentiate these two species. This difficulty in strain identification calls into question previous cultivation-based findings showing S. xylosus to be the dominant Staphylococcus species in poultry litter [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main genus among these is Staphylococcus . It included Staphylococcus aureus (a RG-2 organism), Staphylococcus nepalensis ( 13 ) and Staphylococcus lentus ( 49 ), which are well-known to cause various infections in humans as well as in other animals5758. Therefore, it may pose a threat to the herds of sheep and goats grazing nearby bats’ roosting sites.…”
Section: Discussionmentioning
confidence: 99%
“…Barcode specific fastq files were processed using mothur pipeline57 to obtain fasta and quality file. These two types of the files were quality filtered using following conditions: Size 150–200 bp, homo-polymer max.…”
Section: Methodsmentioning
confidence: 99%